2022
DOI: 10.3389/fimmu.2021.771216
|View full text |Cite
|
Sign up to set email alerts
|

Promotor Hypomethylation Mediated Upregulation of miR-23b-3p Targets PTEN to Promote Bronchial Epithelial-Mesenchymal Transition in Chronic Asthma

Abstract: Chronic asthma is characterized by airway inflammation and irreversible airway remodeling. Epithelial-mesenchymal transition (EMT) is a typical pathological change of airway remodeling. Our previous research demonstrated miR-23b inhibited airway smooth muscle proliferation while the function of miR-23b-3p has not been reported yet. Besides, miRNA is regulated by many factors, including DNA methylation. The function of miR-23b-3p and whether it is regulated by DNA methylation are worth exploring. Balb/c mice we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…This was the first study to utilize DNA methylation-based machine learning to identify a series of asthma-related methylation loci (DECs). Interestingly, the selected methylation signatures were associated with actin cytoskeleton organization and cell-adhesion substrate, shigellosis, and serotonergic synapses, supporting the hypothesis that airway structural reorganization in asthma results from changes in DNA methylation in the epigenetic group [ 28 , 29 ]. Then, ten distinct specific DECs were identified based on RF, and ANN model was built by calculating the weight coefficient of ANN.…”
Section: Discussionsupporting
confidence: 54%
“…This was the first study to utilize DNA methylation-based machine learning to identify a series of asthma-related methylation loci (DECs). Interestingly, the selected methylation signatures were associated with actin cytoskeleton organization and cell-adhesion substrate, shigellosis, and serotonergic synapses, supporting the hypothesis that airway structural reorganization in asthma results from changes in DNA methylation in the epigenetic group [ 28 , 29 ]. Then, ten distinct specific DECs were identified based on RF, and ANN model was built by calculating the weight coefficient of ANN.…”
Section: Discussionsupporting
confidence: 54%
“…Emerging evidence suggests additional targets for miR-23b-3p in non-cancerous diseases, such as neuropilin 1 ( Xia et al, 2020 ), apoptotic protease activating factor-1 (Apaf-1) ( Chen et al, 2014 ), α-synuclein (Geng et al, 2023), and phosphatase and tensin homolog (PTEN) ( Guo et al, 2022 ). Among these, Apaf-1 mediates apoptosis via recruitment and activation of caspase-9 by binding with cytochrome c .…”
Section: Mir-23b-3p Participates In Multi-pathway Crosstalk For Ad Th...mentioning
confidence: 99%
“…Previous studies confirmed that miRNAs play an essential role in allergic diseases by influencing Th1/Th2 polarization and Tregs cell/Th17 cell imbalance, promoting epithelial chronic inflammation and tissue remodeling, and activating intrinsic immune cells [ 11 , 27 , 28 ]. Recently, researchers screened and validated various miRNAs that affected the development of AS by regulating immune cell function and promoting the release of inflammatory mediators [ 29 31 ]. Mattes et al [ 32 ] reported that airway hyperactivity and inflammation might be reduced by inhibiting miR-126 expression, which could affect CD4 + T cell differentiation towards Th2 and the release of inflammatory cytokines.…”
Section: Ncrna and Asmentioning
confidence: 99%